A review on illegals and the stateless in Sabah - Narinderjeet Kaur; Syed Sharizman Syed Abdul Rahim; Mohd Yusof Ibrahim; Mohammad Saffree Jeffree; Mazlinda Musa (2019)
Illegal immigrants refer to the migration of people into a country in ways that violates its immigration laws. A stateless person is a person who is not considered as a national by any state under the operation of its law. Interestingly, many who are stateless have never even crossed an international border. The term illegal is very loosely used in places like Sabah where it is interchanged with statelessness. As of 13 November 2018, it was estimated that there are about 12 million stateless people in the world. This review seeks to understand the current demographic situation in Sabah along with the public health repercussions of this demographic change and also to look into the success stories from around the world along with the recommendations from United Nation in solving this matter. Methods: The method used is reviewing of literature of previous studies conducted on statelessness and illegals. Local as well as international studies were reviewed. The data base used was ProQuest. Results: This review identified that one third of Sabah’s population consists of non-locals and in the past 27 years, about half a million illegal immigrants have been deported from Sabah. These numbers pose major public health repercussions from the economic, crime and health point of view. The way forward involves incorporating the United Nation Action plan with the local requirements and settings. Despite challenges, Sabah is trying its best to curb this issue and the Public health repercussions through various initiatives. We have also identified that more public health actions can be taken to reduce the negative effects. Conclusion: Dealing with the stateless and illegals is a delicate matter and there is no one way to solve it. Every country and every state are unique therefore the methods used must be tailor made. This is not something that can be solved within a short period of time and therefore persistence and perseverance is very much needed to tackle this global issue.